(untitled) (Contrastive Linguistics, 2024)
Диляна Денчева. Фразеологизмите в съвременната българска поезия. София: УИ „Св. Климент Охридски“. 2023. 198 с. The reviewed monography by D. Dencheva is a contributing study in the fields of Bulgarian stylistics and phraseology. The author analyzes rich empirical material from the texts of contemporary Bulgarian poets and makes generalizations about the ways in which phraseological units function in the complex fabric of the poetic text. The author does not use an established theoretical framework, but in the course of the research develops her own methodology, which, together with the in-depth readings of the individual texts, takes us through the intricate ways in which phraseological units fit into modern Bulgarian literature.